(untitled) (Digital Health & Telemonitoring Advances E: 3117-6461 | P: 3117-647X, 2026)
Real-time remote neonatal monitoring represents a significant breakthrough in modern pediatric and neonatal healthcare, particularly in regions with limited access to advanced medical facilities. This study evaluates the sensor technologies enabling remote neonatal monitoring, examines the clinical accuracy of these systems, and analyzes major implementation barriers in clinical and home-care settings. The research synthesizes biomedical engineering principles, neonatal physiology, digital health innovations, and telemedicine frameworks to provide a comprehensive understanding of current capabilities and limitations. Findings highlight that wearable sensors, wireless physiological monitors, and AI-enhanced vital-sign analytics provide clinically reliable data for neonatal assessment; however, usability issues, device sensitivity, data security concerns, and infrastructural constraints impede wider adoption. The paper concludes by recommending standardization, regulatory reinforcement, and adaptive neonatal-focused technologies to ensure reliable and equitable remote monitoring.